'Smelling' the cerebrospinal fluid: olfactory signaling molecules are expressed in and mediate chemosensory signaling from the choroid plexus. (30th March 2016) - Gonçalves, Isabel; Hubbard, Peter C.; Tomás, Joana; Quintela, Telma; Tavares, Gabriela; Caria, Sandra; Barreiros, Daniela; Santos, Cecília R.A.
Abstract : The olfactory‐type signaling machinery has been known to be involved not only in odorant detection but also in other tissues with unsuspected sensory roles. As a barrier, the choroid plexus (CP) is an active participant in the monitoring of the cerebrospinal fluid (CSF), promptly responding to alterations in its composition. We hypothesized that olfactory signaling could be active in CP, contributing to the surveillance of the CSF composition. We determined the mRNA and protein expression of the major components of the olfactory transduction pathway in the rat CP, including odorant receptors, the olfactory G‐protein (Gαolf), adenylate cyclase 3 and cyclic nucleotide‐gated channel 2. The functionality of the transduction pathway and the intracellular mechanisms involved were analyzed by DC field potential recording electrophysiological analysis, in an ex vivo CP‐brain setup, using polyamines as stimuli and blockers of the downstream signaling pathways. Concentration‐dependent responses were obtained for the polyamines studied (cadaverine, putrescine, spermine and spermidine), all known to be present in the CSF. Transfection of a CP epithelial cell line with siRNA against Gαolf effectively knocked down protein expression and reduced the CP cells' response to spermine. Thus, the key components of the olfactory chemosensory apparatus are present and are functional in murine CP, and polyamines seem to trigger both the cAMP and the phospholipase C–inositol 1, 4, 5‐trisphosphate pathways. Olfactory‐like chemosensory signaling may be an essential component of the CP chemical surveillance apparatus to detect alterations in the CSF composition, and to elicit responses to modulate and maintain brain homeostasis. Abstract : The key components of the olfactory chemosensory apparatus are present and are functional in murine choroid plexus. Polyamines seem to trigger both the cAMP and the PLC‐IP3 signaling pathways. Olfactory‐like chemosensory signaling may be an essential component of the CP chemical surveillance apparatus to detect alterations in the CSF composition, and to elicit responses to modulate and maintain brain homeostasis.